Pembinaan Pemasaran dan Pengelolaan Keuangan pada UMKM Batik Ciwaringin Cirebon - Albari, Albari; Sutrisno, Sutrisno; Nurfaizi, M. Iqbal (Rahmatan Lil ’Alamin Journal of Community Services, 2023)
Batik is an original and typical Indonesian product which has received international recognition as an Indonesian cultural heritage which has been designated by UNESCO. The batik industry has also made a significant contribution to the Indonesian economy, where the number of batik businesses in Indonesia has reached almost 3000 business units. Of this number, 98% is the batik industry managed by small entrepreneurs. After being hit hard by the Covid-19 pandemic, the batik industry is now starting to improve. The aim of this service is to provide guidance in the form of marketing management and financial management as well as assistance to batik MSMEs under the auspices of the Ciwaringin Batik Cooperative, so that their batik business management can be better. The coaching provided is in the form of marketing management, financial management and bookkeeping. Based on the results of training and mentoring, MSME participants have been able to carry out promotions independently or jointly with cooperatives, and there has been a slight increase in sales.